Familiar territory. Neighborhood effects on union formation and fertility in Sweden, 1905–2022. - de Souza Maia, Vinicius ; 0000-0003-3624-9548 (Lund Studies in Economic History, 2025)
Our relationships with others structure many aspects of our lives, especially during important moments such as choosing an education, entering the workforce, forming partnerships or starting a family. While the influence of family and parenting has been widely studied, less is known about the role of non-family connections, such as neighbours. One reason is that the data needed to study these relationships is often difficult to obtain. This dissertation contributes to this field by expanding existing high-quality longitudinal databases with detailed geographic information, allowing for a richer understanding of people’s neighbourhood environments across their lives. Using advanced spatial methods, I construct measures that reflect the social settings in which children grew up and young adults lived, following them to union formation and fertility later in life. The thesis links historical and contemporary Sweden. It studies early 20th-century demographic patterns in Landskrona, a mid-sized industrial city in southern Sweden. It then follows individuals who spent their childhoods in Landskrona during the mid-century and tracks their lives into adulthood. Finally, the study turns to contemporary Sweden, examining national trends in union formation. The findings show that neighbourhoods in the past were less socioeconomically segregated than they are today. Nevertheless, living among high-status neighbours was associated with a greater likelihood of marrying, marrying someone with higher education or social status, and postponing parenthood. These patterns were generally observed across social backgrounds, though some effects were context and outcome dependent. In summary, the findings highlight the role of collective socialisation processes within neighbourhoods, that is, the ways in which individuals are influenced by those around them, both directly and indirectly. The evidence indicates that social interactions in neighbourhood settings are linked to demographic behaviours in adulthood, even in contexts where socioeconomic segregation is relatively low. In light of increasing segregation trends in Sweden and other parts of Europe, this dissertation contributes to ongoing research and policy discussions concerning neighbourhood environments and the influence of non-family social networks on individual life trajectories.
Keywords: neighbourhood effects; union formation; marriage; partner selection; assortative mating; fertility; fertility timing; social-interactive mechanisms; cure models; competing risks; k-nearest neighbours; event-history analysis; Sweden; life course